Comment on effect of spin-orbit interaction on the plasma excitations in a quantum wire - Tavares, Marcos R. S. [UNESP] (American Physical Society (APS), 2005)
We comment on the recent results [Phys. Rev. B 70, 235314 (2004)] showing the dispersion relations of single-particle and collective excitations in quantum wires in the presence of the Rashba spin-orbit interaction (SOI). We claim that those calculations performed in the absence of SOI, and used as a strong reference to the interacting case, are unlikely to be correct. We show the correct ω-q plane of the system in the absence of Rashba SOI. © 2005 The American Physical Society.